Pengaruh Analisis Teknikal, Fundamental, Dan Bandarmologi Terhadap Keuntungan Investor Tahun 2021 Di Bursa Efek Indonesia - Dimas Ainur Rochim, Mochamad; Nur Asiyah, Binti (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
In the current era of globalization, investment activities are something that almost everyone knows. The investment sector and the capital market in Indonesia have grown significantly, this is shown in the stock trading on the Indonesia Stock Exchange which always increases every year. However, in conditions in the field, there are still many people who invest without being equipped with knowledge. They simply follow others for fear of being left behind without doing their own analysis, which results in losses. Therefore, the researcher raised this topic as research material. This study aims to determine the effect of technical analysis, fundamental analysis, and bandarmological analysis on Investor Profits in 2021 on the Indonesia Stock Exchange. The sample in this study were students of FEBI State Islamic University Sayyid Ali Rahmatullah Tulungagung who already had investments in the capital market as many as 88 respondents. The data used are primary data from the results of questionnaires and hypothesis testing using multiple regression analysis. The results showed that partially technical analysis and fundamental analysis had an effect on investors' profits, while bandarmological analysis had no effect on investors' profits. Simultaneously all variables have an effect on Investor Profit.